2009
DOI: 10.1039/b904320a
|View full text |Cite
|
Sign up to set email alerts
|

Controlling responsive emulsion properties via polymer design

Abstract: Subtle changes in copolymer surfactant architecture and chain-end functionality can induce diverse behaviours in pH-responsive branched copolymer-stabilized emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…The presence of an MBA moiety in polymers P1-P3 was confirmed by the presence of broad weak signals corresponding to the methylidene protons around 4.4 ppm, which were similar to those of the substrate and chemical shifts published by Zhang et al [39]. The PEG-DMA and PEG-DMA cross-linker/comonomer structures in the polymers were observed as broad ethylene (-OCH 2 -CH 2 O-) n signals around 3.52 ppm, as described previously [40]. Finally, the NTB moieties in the products were confirmed based on the presence of a narrow signal corresponding to the methyl protons of the t-butyl group [41].…”
Section: Discussionsupporting
confidence: 56%
“…The presence of an MBA moiety in polymers P1-P3 was confirmed by the presence of broad weak signals corresponding to the methylidene protons around 4.4 ppm, which were similar to those of the substrate and chemical shifts published by Zhang et al [39]. The PEG-DMA and PEG-DMA cross-linker/comonomer structures in the polymers were observed as broad ethylene (-OCH 2 -CH 2 O-) n signals around 3.52 ppm, as described previously [40]. Finally, the NTB moieties in the products were confirmed based on the presence of a narrow signal corresponding to the methyl protons of the t-butyl group [41].…”
Section: Discussionsupporting
confidence: 56%
“…These highly viscous suspensions can be easily emulsified with decane to obtain stable oil in water emulsions. The O/W interface is stabilized by the BCS molecules [17] and probably the functionalized SiC particles forming Pickering emulsions as it has been also observed for Al2O3 [14]. Particle size, shape and concentration play a very important role on interfacial stabilization and emulsification and therefore determine the microstructure of the material.…”
Section: (Inmentioning
confidence: 81%
“…We also investigate the best sintering route to preserve the features of the porous architectures while optimizing their consolidation. We optimize the sintering BCS with a composition of PEGMA5-MAA95-EGDMA10-DDT10 was synthesized following the protocol described by Woodward et al [17]. BCS solutions (1 wt/v%) were prepared in distilled water at pH 12 (adjusted with NaOH 1M).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous reports of branched copolymer emulsiers, 23,24 we showed that the dodecanethiol chain transfer agentmediated conventional free radical copolymerisation of oligo(ethyleneglycol) methacrylate (OEGMA, 1), methacrylic acid (MAA) and ethyleneglycol dimethacrylate (EGDMA, 2) generates relatively low molecular weight conjoined polymer structures with multiple hydrophobic chain ends. The multiple dodecyl chain ends were able to strongly interact with the oilphase of dodecane and to form highly stable emulsion droplets in water in the absence of additional surfactants or polymers.…”
Section: Branched Copolymer Emulsier Synthesismentioning
confidence: 99%
“…Branched pHresponsive copolymers were also shown to form large scale objects with remarkable stability and reversible hydrogen bonding between emulsion droplets. 23,24 We hypothesised that analogous branched polymer-stabilised emulsions could be generated in the nanoscale to provide advantages for orallydosed ARVs to enable HIV nanomedicine development. Here, we describe the controlled radical polymerisation synthesis of an amphiphilic branched copolymer able to stabilise nanoemulsions containing dissolved LPV or EFV; the tuning of nanoemulsion droplet sizes; and studies of cytotoxicity, drug permeation using a gut epithelium model and subsequent antiviral activity of the drug compounds showing their potential value as future candidate nanomedicines.…”
Section: Introductionmentioning
confidence: 99%